2012
DOI: 10.1111/j.1346-8138.2012.01559.x
|View full text |Cite
|
Sign up to set email alerts
|

Potential association of single nucleotide polymorphisms in pigmentation genes with the development of basal cell carcinoma

Abstract: The risk of developing skin cancers is dependent on a combination of environmental factors and personal genetic predispositions. Basal cell carcinoma (BCC) has been associated with single nucleotide polymorphisms in several pigmentation genes; however, there is still controversy concerning the mechanism by which these variants may increase the risk of BCC. The pathway may lead to pigmentation alone, but evidence for their independent influence is growing. Using a single base extension protocol, candidate polym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…The gene variant associations with pigmented spots were found to be independent of skin color, similar to what is found for gene variants that are associated with different types of skin cancer (Bastiaens et al, 2001b;Han et al, 2006;Kosiniak-Kamysz et al, 2012).…”
Section: Discussionsupporting
confidence: 79%
“…The gene variant associations with pigmented spots were found to be independent of skin color, similar to what is found for gene variants that are associated with different types of skin cancer (Bastiaens et al, 2001b;Han et al, 2006;Kosiniak-Kamysz et al, 2012).…”
Section: Discussionsupporting
confidence: 79%
“…The additional two positions considered in the third block of VDR, that is, rs11568820 and rs2238136, were shown in this study to further increase the significance of the haplotype in VDR. Gene-gene interactions have been shown in previous studies to affect skin and eye colour as well as modify the risk of basal cell carcinoma [31,32,36,59,91,92]. One of the very few studies examining rs11568820 showed no association with the risk of CMM [82].…”
Section: Discussionmentioning
confidence: 97%
“…The usefulness of low-penetrance susceptibility loci including multiple genes involved in melanogenesis and VDR in the evaluation of the individual risk of CMM will depend on the size of independent information provided by genotypes predisposing to CMM. Notably, carriers of these MC1R variants have also been shown to be at a higher risk of other skin cancers [7,10,11,43,[56][57][58][59]. Here, we selected 12 loci and examined 33 variants in 130 CMM patients (83 women and 47 men) and 707 healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…A diminished MC1R activity, as caused by multiple loss-of-function polymorphisms in MC1R, produces the yellow to reddish pheomelanin, which has a weaker UV shielding capacity than that of the brown to black eumelanin [12]. However, multiple studies have shown loss-of-function MC1R variants significantly associate with age spots, actinic keratosis, and various types of skin cancers in a skin-color-independent and/or UV-exposure-independent manner [6,[13][14][15][16][17][18], and in the present study, we showed that MC1R variants associated with perceived age after skin color and sun exposure adjustments. These observations are in line with previous findings from functional studies suggesting a pleotropic role for MC1R in inflammation [19] and nucleotide excision repair [20], as well as in fibroblasts during wound healing and tissue repair [21], and are consistent with the previously demonstrated UV-independent carcinogenesis mechanism of MC1R via oxidative damage [22].…”
Section: Discussionmentioning
confidence: 99%